Independensi Jabatan Ex-Officio Komisi Kepolisian Nasional dalam Kajian Sistem Ketatanegaraan - Fakhrazi, Muhammad Helmi (Jurnal Yuridis, 2017)
Nowadays in creating new institutions to support the main state institution so many emerging. And the characters of institutions are very diverse, there is not only the fuctions, duties and power that have a new characters, even membership organization structure looks different from the establishment of the institution in general. one of the new institute is a national police commission (Kompolnas), on the one hand Kompolnas aspired as a supervisory institution, but on the other hand the National Police Commission headed by state officials from other agencies (ex-officio). This article will try to assess the analytical descriptive approach, normative juridical authors will describe briefly the independency of the job, in the study of the constitutional system. However, if the chief commissioner of the National Police Commission is of the same people serving other institutions, whether independency Kompolnas institution can run well according aspiration beginning of its formation